Avaliação da aplicabilidade de aromas naturais de caju e cajá na saborização de kombucha - Santos , Nayara Barbosa dos (2023)
Kombucha tea is a refreshing drink with a characteristic flavor, slightly sweet and acidic, consumed all over the world. Praised for its detoxifying and energizing properties, it is obtained in up to 15 days from the first fermentation (F1) of tea sweetened with leaves of the genus Camellia sinensis in which an acidifying solution (starter) is inoculated together with the Symbiotic Culture of Bacteria and Yeasts (SCOBY). From this, the option of incorporating different flavors to the drink is available through infusion techniques of fruits, pulps, spices or extracts in a second fermentation stage (F2). Therefore, it is important to control some variables that influence the process, such as temperature, luminosity, oxygenation and asepsis, in parallel with the monitoring of parameters such as pH, total acidity, alcohol and sugar content through specific methodologies and devices. In this context, the present research applies to Bauá Kombucha® with the objective of evaluating the use of natural aromas in the flavoring of non-alcoholic kombucha, as substitutes for commercial pulps commonly used on an industrial scale. In this way, we sought to emphasize aromas and flavors added to the beverage, also providing standardization and stability to the batches. The Regional flavors of Cajá and Cashew, already commercialized by the brand, were selected due to their representativeness and availability in the market. Thus, tests were outlined in three fundamental parts, to verify the influence of the carbohydrate concentration on the F1 (Preliminaries), determination of the best concentrations of natural aromas and pulps of both flavors for F2 (Initials of bench) and kinetic evaluation of the maturation phase and natural gasification of the unpasteurized drink. In all cases, the recipes and concentrations used were hidden for reasons of secrecy, parameters such as pH, TSS, ATT, Ratio, color, density, foamability and CO2 production being evaluated. Finally, we proceeded with the nutritional characterization of the best results obtained, also in terms of total phenolics, antioxidant activity and minerals. The results obtained were quite strong, demonstrating a high antioxidant capacity and the presence of new phenolic compounds characterized by chromatography. Despite this, there were no significant indications that indicate the replacement of pulps by natural aromas in the flavoring of cajá and cashew kombucha.